Turcish publicism and is role society (Journal of Oriental Studies, 2017)
The article is about Turkish publicistical style genres, types, role in society and important sides. Publicistic style is the most widely used andpopular style. Publicistic style-political, cultural, sports, etc. in the framework  of a functional language, serving a kind of public relations. Publicisticstyle is containedpolitical information in various newspapers, magazines, brochuresin Turkish society. There are issues specific to Turkish publicisticstyle: imagery and political clarity. These matters occur to formulate people’s consciousness, public opinion for social purpose.